Enhancement of artemisinin production with ultraviolet B radiation and dimethyl sulfoxide in low-artemisinin producing (136P) and high-artemisinin producing (Hyb8001r) chemotypes of Artemisia annua L. - Kam, Melissa Yit Yee (2021)
The antimalarial sesquiterpene, artemisinin (ART) is associated with a variety of novel biological properties and therapeutic applications. Emerging from the fact that ART production in Artemisia annua Linn. occurs in trace amounts and its synthesis compartmentalised, the irregular agricultural supply often results in market fluctuations and reductions in ART inventory. While heterologous biosynthesis and semi-synthesis were advantageous in certain aspects, these approaches remained disadvantageous in terms of productivity and cost-effectiveness, respectively. Semi-synthetic production has the advantage of scale-up manufacturing but the recovery and purification of the microbially-derived starting substrate as well as the additional downstream chemical processing to produce semi-synthetic ART are costly compared to conventional processing of plant-derived ART. Therefore, further improvement in ART production is required to supplement the agricultural production gap, lower production costs and stabilise ART supply. This thesis focuses on the development of an alternative ART resupply strategy utilising elicitation combined with mass clonal propagation via plant cell technology and vegetative propagation by stem cuttings for a non-commercial, European low-artemisinin producing (LAP) A. annua variety (136P). Elicitation efficiencies of ultraviolet B (UV-B) at different exposure durations (0, 1, 2, 3, 4, 5 h) and dimethyl sulfoxide (DMSO) of increasing concentrations (0, 0.1, 0.25, 0.5, 1, 2% [v/v]) on 136P were investigated. Although stress induction on suspension cultures of A. annua with either abiotic elicitor did not elicit ART synthesis or augment its production, elicitation of soil-grown 136P plants showed positive preliminary results. The exposure of plants to 1 h of UV-B radiation and 0.25% (v/v) of DMSO resulted in 93% (5.0722 ± 0.9947 mg g-1 dry weight [DW]) and 155% (12.7730 ± 0.2317 mg g-1 DW) enhanced ART content, respectively. In subsequent elicitation studies, the production of ART in soil-grown 136P plants was not enhanced under UV-B or DMSO treatment, which was hypothesised as a result of plant resource allocation for the investment in growth. Further gene expression analysis provided new insights into the metabolic status of this LAP chemotype in response to the stresses and during defensive stimuli. This valuable information has the potential to improve methods for increasing ART content in LAP cuttings via elicitation as alternative propagation materials aside from the reliance on commercial hybrid seeds. Given the potential of stress-induced 136P plants to produce ART at levels comparable to a high-ART hybrid (Hyb8001r), this strategy may possibly serve as a complementary approach to the current agricultural supply.